Reimagining School Management: Integrating Local Wisdom to Enhance School Quality in the Society 5.0 Era - Dahlia Rineva Puspitasari; Munir Munir; Udin Syaefudin Sa’ud; Sururi Sururi (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
The aim of this study is to develop a school management model rooted in sabilulungan local wisdom to enhance school quality sustainably in the society 5.0 era. This strategy is crafted to address the complexities of contemporary educational management, necessitating a synergy between advanced technology and local cultural values. This study employs a Research and Development (R&D) methodology utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework. Data collection was conducted using questionnaires, in-depth interviews, observations, and documentation studies, employing methodological and source triangulation to enhance the validity of the findings. The study's findings suggest that school management incorporating sabilulungan values, including mutual cooperation, deliberation, and togetherness, enhances the efficacy of planning, implementation, organization, and supervision inside educational institutions. This model enhances community engagement, fortifies a humanistic organizational culture, and elevates overall educational outcomes. The model’s implementation has demonstrated efficacy in the social and technological environment of West Java, especially sundanese culture, bolstered by the support of administrators, teachers, and school communities as critical success factors. This research is innovative in its integration of POAC management concepts, local values of sabilulungan, and technological requirements of the Society 5.0 period into a singular, usable model framework. This research presents theoretical advancements in the formulation of management models grounded in local wisdom and proposes practical methods for enhancing adaptable, participatory, and contextual school management.